The grain size effects on the photoluminescence of ZnO/alpha-Al2O3 grown by radio-frequency magnetron sputtering - Kim, KK; Song, JH; Jung, HJ; Choi, WK; Park, SJ; Song, JH (AMER INST PHYSICS, 2000)
ZnO thin films were epitaxially grown on alpha-Al2O3 (0001) substrate by radio-frequency (rf) magnetron sputtering. Among the ZnO films deposited at 550 degrees C, the film deposited at 80 W has the narrowest full width half maximum (FWHM) of x-ray diffraction (XRD) theta-rocking curve, 0.16 degrees, indicating a highly c-axis oriented columnar structure. The FWHM of XRD theta-rocking curve of the ZnO film deposited at 120 W and 600 degrees C was 0.13 degrees with a minimum channeling yield, 4%-5%. In photoluminescence (PL) measurement, only the sharp near band edge emission was observed at room temperature (RT). The FWHM of PL peak was decreased from 133 to 89 meV as rf power increased from 80 to 120 W at 550 degrees C, and that of film deposited at 120 W and 600 degrees C showed 76 meV which is lower value than any other ever reported. These PL results were somewhat opposite to that of XRD. From transmission electron microscopy analysis, grain size and defects were found to affect the PL properties. In this study, the PL property of undoped ZnO thin films is discussed in terms of the crystalline structure and the size of grain. (C) 2000 American Institute of Physics. [S0021-8979(00)06303-9].
Keywords: GAN; ZNO